Comparisons of perceived images in multiview and integral photography based three-dimensional imaging systems - Son, Jung-Young; Saveljev, Vladmir V.; Kim, Kyung-Tae; Park, Min-Chul; Kim, Sung-Kyu (JAPAN SOC APPLIED PHYSICS, 2007)
The imaging properties of multiview and integral photography based three-dimensional imaging systems are compared on the basis of their viewing-zone-forming principles. It is confirmed that 1) the images projected to the viewers' eyes in IP and the multiview have a conjugate relationship between them and 2) the quality of the image projected to viewers' eyes in integral photography will be increased if the image resolution of each lenslet in the microlens plate is minimized by reducing the field of the view angle of the microlens plate and the number of lenslets in the plate is increased.
Keywords: RESOLUTION LIMITATION